2018
DOI: 10.33245/2310-9270-2018-142-2-40-46
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spring wheat varieties by the productivity elements in the Forest Steppe of Ukraine

Abstract: The article highlights the problems of forming the economically valuable features which affect the productivity of soft spring wheat varieties. The structural analysis data reveal that the number of spikelets in the investigated varieties of wheat ears ranged within 15.4 pcs. In the Triso variety to 20.1 pcs. in the Kharkivska 30, the rate for the variety standard was registered 16.0. The variability amplitude rate varied from 2.0 spikelets in Hordynya and Simkoda Myronivska varieties to 5.0 in the Kharkivska… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
2
0
1
Order By: Relevance
“…of spikes.m-2 was (187.0) in the cultivar Karoneyah under Rain-fed Irrigation. These results are in agreement with what was stated by [9] and by [10] that the trait of the No. of spikes per plant under drought conditions in Mediterranean environments is considered as one of the most important indicators of grains yield in durum wheat.…”
Section: No Of Spikesm -2supporting
confidence: 94%
See 1 more Smart Citation
“…of spikes.m-2 was (187.0) in the cultivar Karoneyah under Rain-fed Irrigation. These results are in agreement with what was stated by [9] and by [10] that the trait of the No. of spikes per plant under drought conditions in Mediterranean environments is considered as one of the most important indicators of grains yield in durum wheat.…”
Section: No Of Spikesm -2supporting
confidence: 94%
“…Through our observation of the average values of the cultivars in Table (10), the Firat-93 cultivar outperformed the other cultivars in weighing 1000 grains with an average value of (39.52 gm), while the Kardenenay and Svevo cultivars recorded the lowest values (25.00, 25.30 gm), respectively, as noted. The cultivars grown under Supplementary Irrigation gave the highest weight of 1000 grains (34.18 gm), with a significant difference from the average of Rain-fed-Irrigation (28.47 gm).…”
Section: Weight Of 1000 Grains Gmsupporting
confidence: 53%
“…Dry conditions in recent years have led to low yields of spring wheat, which did not exceed 3.52 t ha -1 . Modern varieties of spring wheat of foreign and domestic selection, included in the State Register of Plant Varieties of Ukraine, have a high yield potential and can provide a yield of 5-8 t ha -1 in production conditions (Lozinska and Fedoruk, 2017;Radchenko et al, 2023). As a result of the research conducted by Sumy National Agrarian University, it was found that the yield according to the experiment options ranged on average from 4.07 t ha -1 to 5.63 t ha -1 (LSD 05 = 0.12).…”
Section: Resultsmentioning
confidence: 99%
“…During formation of grain yielding capacity, the excess leaf surface will not contribute to high yield of the crop, as part of leaves will be shaded by its upper circles (Zhemela and Shevnikov, 2013). According to the results of Lozinska and Fedoruk (2017), the index of leaf surface area of spring wheat changed significantly depending on variety assortment, and the largest leaf surface area was formed in the earing phase in the range of 33.4-34.1 thousand m 2 ha -1 . In the studies of Sumy National Agrarian University, it was found that in the tillering phase of spring wheat, the leaf surface area was 4.0-6.0 thousand m 2 ha -1 .…”
Section: Resultsmentioning
confidence: 99%